Monitoring of infliximab treatment in inflammatory bowel diseases – basic knowledge and current data based on clinical trials in a population of Polish patients - Pękala, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
Introduction and aim. Infliximab is the oldest biological drug belonging to the group of tumor necrosis factor antagonists. Despite the availability of many new biological therapies, this drug still plays an important role in the treatment of inflammatory bowel diseases. However, a significant problem related to pharmacotherapy is the high inter-individual variability of the response. Material and methods. This study presents results of the research on the treatment with infliximab in the inflammatory bowel disease (IBD) patients including our own experience in Polish IBD patients. Analysis of the literature. Therapeutic failure while using infliximab can be attributed partly to inadequate serum concentrations of the drug and the development of anti-drug antibodies. Many studies have attempted to find a relationship between the specific level of infliximab and the achieved healing effect. These analyses show that the optimal level of the drug differs depending on the type of disease, its phenotype, and therapeutic goal and that the optimization of infliximab therapy remains an open topic. Two studies involving the population of Polish IBD patients examined the level of infliximab during and after induction, as well as the frequency of anti-drug antibodies. Two studies involving a population of Polish IBD patients examined the level of infliximab during and after induction, as well as the frequency of anti-drug antibodies. These studies demonstrated the need for monitoring infliximab treatment at weeks 6 and 14. Conclusion. Reactive monitoring is believed to enable the most rational treatment decisions; however, experts also recommend that proactive monitoring should measure infliximab concentrations at the end of induction and at least once during maintenance treatment.
Keywords: infliximab; Crohn’s disease; therapeutic drug monitoring; ulcerative colitis